A Method of Finding Source Function for Inverse Diffusion Problem with Time-Fractional Derivative. (25th May 2016) - Gülkaç, Vildan
Abstract : The Homotopy Perturbation Method is developed to find a source function for inverse diffusion problem with time-fractional derivative. The inverse problem is with variable coefficients and initial and boundary conditions. The analytical solutions to the inverse problems are obtained in the form of a finite convergent power series with easily obtainable components.